2018
DOI: 10.1136/tobaccocontrol-2018-054249
|View full text |Cite
|
Sign up to set email alerts
|

Graphic health warnings on tobacco packets and containers: compliance status in Bangladesh

Abstract: ObjectiveThis study describes and analyses compliance with tobacco product graphic health warning (GHW) legislation introduced in Bangladesh in March 2016.MethodsA survey based on a structured questionnaire was conducted in April 2016 (immediately following the law coming into force), and 8 months later in November 2016, in eight divisional cities in Bangladesh. Five stores from three categories of retailers of combustible and smokeless tobacco products were surveyed, providing a total of 120 completed questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…In addition, most participants suggested having a standard packaging system for ST products with proper GHWs and information of contents to the public. The findings of our study coincide with the study conducted by Rahman et al (2019) to observe compliance with tobacco product GHWs in Bangladesh [26]. The study found that 53% of zarda packets and 58% of gul packets had 50% of the packet area covered by GHWs.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, most participants suggested having a standard packaging system for ST products with proper GHWs and information of contents to the public. The findings of our study coincide with the study conducted by Rahman et al (2019) to observe compliance with tobacco product GHWs in Bangladesh [26]. The study found that 53% of zarda packets and 58% of gul packets had 50% of the packet area covered by GHWs.…”
Section: Discussionsupporting
confidence: 90%
“…Graphic health warnings are intended to prompt smokers to think that they could contract diseases depicted in the pictures. Worldwide, GHWs were proven effective in prompting smokers to think about the dangers of smoking which are associated with increased intention to quit [11][12][13] . Moreover, this study showed that non-exposure to health warnings leads to higher odds of intention to continue smoking among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…activities involving corporate social responsibility such as charity-giving to encourage smoking, particularly among youth) and weak enforcement of non-tax tobacco control measures (e.g. non-compliance of graphic health warnings on tobacco packaging) in the country 39 , 40 . More research is needed into factors affecting trends in consumption of tobacco.…”
Section: Lessons Learntmentioning
confidence: 99%